SCANDIUM EXTRACTION PROCESS FROM RED MUD PT. ICA BAUXITE REFINERY PLANT USING HIGH PRESSURE ACID LEACHING IN SULFURIC ACID SOLUTION - Reynaldo Kanekaputra, Mikhael
Scandium is one of the metals whose existence is rare and is needed in the development of advanced technology so that it has an expensive price. Generally, scandium is obtained from the by-products of other metal production processes. One of raw material sources of scandium is red mud produced by bauxite refining to alumina. Currently, there are few studies that discuss the process of extracting scandium from red mud using High Pressure Acid Leaching (HPAL) and no one has reported it for red mud from Indonesia. This research was conducted to determine the effect of several variables, namely sulfuric acid concentration, time, temperature and solid percentage on the extraction of scandium from the red mud of the bauxite refining plant of PT. ICA using HPAL Red mud sample preparation was carried out through a process of homogenization, drying, grinding, sifting, and sampling. The characterization of red mud was carried out by analyzing water content, X-Ray Diffraction (XRD), X-Ray Fluorosence (XRF), and Inductively Coupled Plasma (ICP). Furthermore, experimental design was carried out using the Taguchi orthogonal array L9 method (34). A series of HPAL experiments were carried out by varying the dosage of sulfuric acid addition (0.5; 1; and 1.5 M), leaching time (1, 2 and 4 hours), temperature (200oC, 220oC and 240oC), solid percentage (10, 20, and 30% w/w). The extraction percentage of Sc and Fe from the leaching process was processed using the Taguchi Method and ANOVA to determine the optimum conditions and the significance of the effect of each variable on the extraction percentaged of Sc and Fe. Based on the results under optimum conditions, experiments were carried out again to validate the effects of the variable acid concentration (0.5; 1; 1.5; and 2 M), leaching time (30, 60, 120, and 240 minutes), and temperature (180oC, 200oC, 220oC and 240oC) on the extraction percentages of Sc and Fe, as well as other metal impurities (Al, Si, Ti).. The optimum conditions for scandium extraction were obtained at a concentration of 1.5 M sulfuric acid, a leaching time of 1 hour, a temperature of 200oC, and a 10% solids percentage. The percentage of Sc extraction obtained from validation experiment at optimum condition was 90.97%. By using ANOVA method, the contribution of acid concentration, leaching time, temperature and solid percentage on Sc extraction was 21.2%, 0.3%, 16.4%, and 62%, respectively. The results of the validation experiments showed that the experiment at optimum conditions gave the highest percentage of Sc extraction. The dissolution rate of scandium in the red mud leaching process was 3.6 mg/hour at temperatures of 180°C and 200°C and 4.8 mg/hour at temperatures of 220°C and 240°C and showed a parabolic relationship between percent extraction and leaching time.